Diskursus Penafsiran Milkul Yamin di Kalangan Ulama Klasik dan Kontemporer: Teks dan Konteks - Firdaus Eka Putra, Andi (USRATY : Journal of Islamic Family Law, 2024)
The institutionalised ownership of slaves (milkul yamin) is one of the focuses of the Quranic critique of the culture of exploitation and domination in Arabia. The Quran views that it must be eliminated immediately even though it is done gradually, including through expiation in the form of freeing slaves and allowing masters to have sex with their personal slaves as stated in several verses of the Quran. The concept of milkul yamin is interpreted with various views by classical and contemporary scholars, even with interpretations that go beyond previous scholars towards non-marital sexual relations. This research will reveal how classical and contemporary scholars interpret the concept of milkul yamin found in the Quran and hadith both in text and context. This research is a qualitative type of library research with data derived from sources related to the concept of milkul yamin in the form of books, books, articles and various writings in online media then analysed using descriptive methods. The results showed that the majority of classical and contemporary scholars viewed the verses on slavery as Islam's attempt to raise the status of slaves from religious prisoners of war at that time. As well as a way for Islam to gradually abolish the practice of slavery that has been entrenched and rooted in jahiliyyah Arab society. Meanwhile, according to Muhammad Syahrur's reinterpretation, it is more subjective, influenced by modern culture and civilisation, and does not carefully consider the historical meaning of the verse and the main message contained in the verse.